Bogus electronic manufacturing and consumers confront a rising tide of counterfeit electronics. - Pecht, M. (IEEE spectrum)
This paper discusses the growing concern over the counterfeiting of electronics components and systems. Three key factors are identified as the root cause of this problem: the shift of manufacturing to China where intellectual property laws are not strictly enforced and supply chains are convoluted; the growing sophistication of technology that enables cheaper and more convincing fakes; and the rise of the Internet as a marketplace, allowing buyers and sellers make fast trades without ever meeting face to face. As many companies are learning the hard way, counterfeiting requires a constant, deliberate, and multifaceted effort, vigorous monitoring of potential trouble spots, and judicious use of anticounterfeiting technologies.